Clinical application of pharmacogenetic markers for drug dosing. - Sukasem, C. (Chulalongkorn Medical Journal, 2023)
Human polymorphic nature has an effect on individual drug response and adverse drug reactions (ADR). These variations include insertions, deletions, copy number variations and single nucleotide polymorphisms (SNPs) that affect gene expression and activity of drug metabolizing enzymes. Currently, there have been extensively studies and well characterized relationships between genetic variations and drug metabolism, and drug toxicity. Consequently, the application of patient genetic background to individualized therapy has been achieved at the practical level. Moreover, information on pharmacogenetics will be a crucial factor in medical practices in the near future. Therefore, the focus of this article will be on recent evidence on pharmacogenetic markers involved in drug response and doses appropriate, clinical application and impact on medical economy. It is expected that a wider understanding of existing evidence by medical profession is essential to increase their utilization.